(untitled) (Research in Agriculture Livestock and Fisheries, 2024)
Buffalo ovaries were collected from abattoirs in Dhaka city. During collection, left and right ovaries were identified and recorded. After processing, the ovaries were categorized as (i) ovaries without corpus luteum (CL) and (ii) ovaries with corpus luteum (CL). Ovaries were then evaluated based on length (cm), width (cm), weight (g), total number of follicles on the surface of each category of ovaries, number of follicles aspirated, and total number of cumulus-oocyte-complexes (COCs). The experiment’s findings indicated variations in the parameters related to the left and right ovarian categories. The CL% (27.12±0.11%) found highest in the right compared to the left (3.24±0.11%). The length (cm), width (cm), and weight (g) (2.75±0.06, 2.17±0.05, 4.74±0.13) were found significantly (p<0.01) higher in the right ovaries compared to left (2.27±0.06, 1.77±0.05, 3.90±0.13). The number of follicles in total and number of follicles aspirated were found significantly (p<0.01) higher (6.35±0.16 & 5.47±0.16) in the left ovaries compared to right (6.16±0.16 & 4.18±0.16). The number of normal COCs and total COCs was significantly (p<0.01) higher in the left ovaries (0.98±0.134 & 1.57±0.17) compared to right (0.84±0.16 & 1.54±0.17). The abnormal COCs were significantly (p<0.01) higher in the right ovaries (0.75±0.107) compared to left (0.57±0.107). Regarding ovarian categories; (76.47±0.01%) showed ovaries without CL, whereas (23.53±0.01%) showed ovaries with CL. The weight (g) was found significantly (p<0.01) higher in ovaries with CL (4.73±0.12) compared to ovaries without CL (4.36±0.12). The number of follicles in total and aspirated were found significantly (p<0.01) higher in ovaries without CL (7.60±0.14 & 5.28 ±0.14) compared to ovaries with CL (4.29±0.14 & 2.29±0.14). Regarding the number of total COCs, ovaries without CL showed a significantly (p<0.01) higher number of total COCs (1.41±0.11) compared to ovaries with CL (1.17±0.11), where the number of normal and abnormal COCs (0.55±0.01 & 0.86±0.03) were found significantly (p<0.01) higher in ovary without CL compared to the ovary with CL (0.5±0.01 & 0.54±0.03). Finally, it can be concluded that the left and ovaries without CL contain more follicles in total and aspirated and normal COCs. Thus, the left and ovaries without CL are best for collecting quality COCs in buffaloes. Res. Agric. Livest. Fish. Vol. 11, No. 2, August 2024: 125-135